Active management, value investing and pension fund performance - Luis Otero-González; Pablo Durán-Santomil; Rubén Lado-Sestayo; Milagros Vivel-Búa (European Journal of Management and Business Economics, 2021)
Purpose – This paper analyses whether the active management and the fundamentals of the pension fund allow products that beat their peers to be identified in terms of risk-adjusted performance. Design/methodology/approach – The sample is composed of all the pension funds active in the period 2000 to 2017 investing in the Eurozone. What this means is that a greater similarity is guaranteed in terms of benchmark, assets available for investment and currency. All the data have been retrieved from the Morningstar Direct database. Findings – The paper reveals that the degree of concentration and value for money are important determinants of performance. In this sense, the strategies of investing in concentrated portfolios that differ from the benchmark and with undervalued assets in terms of price earnings ratio (PER)-return on assets (ROA) achieve better results. Originality/value – This is one of the few papers that shows the effect of active management and value investing strategies’ on the performance of pension funds. 研究目的 – 本文旨在分析、我們能否根據退休基金的積極管理及其基本原理, 找到就風險調整表現而言之最優勝產品. 研究設計/方法 – 我們的樣本包括於2000年至2017年期間活躍於歐元區內投資活動的所有退休基金。這意味著、樣本確保了相關之退休基金就基準、可供投資的資產及貨幣而言、均擁有較大的相似性。所有數據均從晨星基金資料庫檢索得來的。. 研究結果 – 本文顯示、集中程度和價值比率是決定表現的重要因素。在這個意義上說，如投資在與基準不同的及附有就本益比 – 資產收益率 (PER - ROA) 而言被低估的資產的那些集中投資組合上, 這會是效果較佳的策略. 研究的原創性 – 探討積極管理和價值投資策略如何影響退休基金表現的學術研究為數不多, 本文乃屬這類研究。.